(untitled) (Eurasian Scientific Herald, 2022)
The inclusion of important professional emotional features in the pedagogical dialogue in the educational process serves to ensure the effectiveness of this process. Solving an emotionally stable situation during pedagogical communication among future teachers has a positive effect on the morale of the participants in the communication process. This article reveals important professional emotional features of the teacher in the process of communication.